Melampaui Akal dan Indera: Rekonstruksi Epistemologi Al-Ghazālī Berbasis Qalbu dan Relevansinya bagi Pendidikan Islam Kontemporer - Muhammad Sholeh Afif; Triyo Supriyatno (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Contemporary Islamic education in Indonesia faces a critical juncture between technological opportunities and epistemological crises. The massive expansion of digital access has intensified the dominance of sensory knowledge (ilmu ḥissiyah) and rational-instrumental knowledge (ilmu ʿaqliyah), while marginalizing the spiritual-moral dimension centered on the qalbu. This condition is empirically reflected in the rising prevalence of emotional disorders among adolescents, spiritual emptiness, existential crises, and psychological pressure exacerbated by digital culture and the shift to online learning during the COVID-19 pandemic. Over-reliance on sensory and technological approaches without strengthening the qalbu has resulted in psychospiritual dysfunction among learners. In this context, Al-Ghazālī's epistemology offers a relevant critique and reconstruction. Through his works such as al-Munqiḍ min al-Ḍalāl and Iḥyāʾ ‘Ulūm al-Dīn, Al-Ghazālī constructs a hierarchical and integrative epistemological framework, placing sensory and rational knowledge under the leadership of a purified qalbu that receives divine illumination (ilm ladunī). The qalbu functions as the